The compliance and cost-effectiveness of smartphone urinalysis albumin screening for people with diabetes in England. (3rd July 2020) - Shore, Judith; Green, Michelle; Hardy, Andrew; Livesey, Deborah
ABSTRACT: Background: People with diabetes are at increased risk of developing chronic kidney disease (CKD) and should undergo annual screening, but adherence is poor. A home urinalysis self-test has been developed to improve compliance with screening. The objective of this paper is to report on a clinical evaluation and economic analysis of home urinalysis self-testing. Research design and methods: People with diabetes who had not undergone screening within the previous 18 months were recruited to a single-arm clinical evaluation to assess the uptake and compliance of home urinalysis self-testing. An economic evaluation assessed the likely cost-consequences of the use of home urinalysis self-testing over a lifetime time horizon. Results: A total of 2, 196 people with diabetes were contacted as part of the clinical evaluation. Of these, 695 people agreed to be sent a home urinalysis self-testing kit and 499 people completed and returned the test. Cost savings of £2, 008 per person were estimated over a lifetime due to increased CKD diagnosis and reduced progression to end stage renal disease. Conclusions: Home urinalysis self-testing of ACR in people with diabetes is estimated to be a cost-effective use of NHS resources in England in people who would otherwise not comply with standard care.